Mites (Acari, Gamasida) of the Narew National Park - Gwiazdowicz, Dariusz J. (1966– ); Szadkowski, Rafał; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum and Institute of Zoology, PAS, 2000)
This paper presents a list of mites of the Gamasida order in the Narew National Park.
Bibliogr. p. 95
P. 91-95 ; 24 cm
Abstarct in Polish. Taxa in Latin.
Keywords: Mesostigmata; mesostigmatid mites; gamasids; arachnids; Arachnida; Poland; mites and ticks; acarines; Acarina; Acari; new taxa to the Polish fauna; mites; Gamasida; Narew National Park